Tinjauan Filosofis Sumber Hukum Islam dan Peranannya dalam Mendukung Transaksi Pasar Modal Syariah Indonesia - Mukhlis Lubis; Zaimmudin Asmawi; Mohamad Anton Athoillah (Program Studi Hukum Keluarga Islam (Ahwal Syakhshiyyah), Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2023)
This article seeks to explore how the wisdom of tasyri' is able to moderate the understanding of the sources of Islamic law related to Islamic securities transactions in the Indonesian Capital Market using Ali Ahmad al-Jurjawi's framework in his book; hikmatu at-tasyri' wa falsafatuhu. This article arrives at a thesis that the sources of Islamic law, both naqli and aqli, especially those related to Islamic securities transactions in the Indonesian Capital Market, are full of wisdom and sharia values that improve relationships to God and relationships between fellow humans. This thesis - at the same time - is considered a novelty of this paper, because previous research conducted by Ali Ahmad al-Jurjawi did not elaborate on the wisdom of tasyri' contained in the moderation of understanding the sources of Islamic law related to Islamic securities transactions in the Indonesian Capital Market. This can be seen from two important things. First, the wisdom of tasyri' related to Islamic securities transactions in the Indonesian Capital Market can be identified, codified and practiced through the movement of moderation in understanding the sources of Islamic law. Second, the wisdom must contain the value of maslahat in general and keep many parties, both corporations and individuals, from the potential for harm or large losses due to not responding to economic movements and technological developments as well as market needs, so that capital market laws, compilations of sharia economic law, financial services authority regulations, and fatwas are made to respond to these interests.